Riding the waves of disruption - PAN, Gary (Institutional Knowledge at Singapore Management University, 2017)
For organisations, the need to respond to disruption, digital or otherwise, has never been greater – from re-defining the way they interact with customers to delivering services and products. While disruption presents significant opportunities for businesses, the biggest risk is not taking any action at all. A radical industry shift might be required in some cases and spending time thinking about this is critical. Organisations and individuals can shield themselves from disruption by building the skills and agility to move and adapt quickly, protecting their future in the short and long term. Against this backdrop, CPA Australia and Singapore Management University School of Accountancy believe there is merit in contributing to the eco-system by equipping corporate decision makers with the necessary insights to understand how to anticipate and respond to digital disruption. Hence, this toolkit aims at accounting and finance professionals, directors and senior management in SMEs, as well as business advisors at large.